2018
DOI: 10.4143/crt.2017.210
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Charcoal Tattooing of Cytology-Proven Metastatic Axillary Lymph Node at Diagnosis and Sentinel Lymph Node Biopsy after Neoadjuvant Chemotherapy in Breast Cancer Patients

Abstract: PurposeSentinel lymph node biopsy (SLNB) can be performed when node-positive disease is converted to node-negative status after neoadjuvant chemotherapy (NCT). Tattooing nodes might improve accuracy but supportive data are limited. This study aimed to investigate the feasibility of charcoal tattooing metastatic axillary lymph node (ALN) at presentation followed by SLNB after NCT in breast cancers.Materials and MethodsTwenty patientswith cytology-proven node metastases prospectively underwent charcoal tattooing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 31 publications
3
56
0
6
Order By: Relevance
“…15 Other methods of localization of the axillary LN using charcoal suspension, Magseed or Savi Scout radar reflectors have been described and their respective published feasibility studies reveal high IRs. 10,17,18 The clipped node uptake of blue dye was only 58% and 83% for radioactive tracer. The clipped node was not retrieved as the SLN in 14% of patients in our series.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…15 Other methods of localization of the axillary LN using charcoal suspension, Magseed or Savi Scout radar reflectors have been described and their respective published feasibility studies reveal high IRs. 10,17,18 The clipped node uptake of blue dye was only 58% and 83% for radioactive tracer. The clipped node was not retrieved as the SLN in 14% of patients in our series.…”
Section: Discussionmentioning
confidence: 96%
“…They reported an IR of 97% where three seeds were not retrieved . Other methods of localization of the axillary LN using charcoal suspension, Magseed or Savi Scout radar reflectors have been described and their respective published feasibility studies reveal high IRs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Magseed is not compatible with standard surgical instruments. Charcoal tattooing of positive lymph nodes at the time of biopsy has also been reported . However, there may be a small risk of charcoal migration, potential nonvisualization of the tattoo at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The removal rate of SMART in our study was comparable to the rates reported for other localization agents. The radioactive seed, wire and tattooing techniques had a removal rate of nodes of 97%-100%, 6,20 71%-100%, 11,13,21,22 and 83%-100%, 16,17 respectively.…”
Section: Discussionmentioning
confidence: 99%